PERAN SEKOLAH ISLAM TERPADU DALAM PEMBENTUKAN KARAKTER RELIGIUS SISWA (Study kasus di SDIT Islam Terpadu Permata Bunda GedungMeneng Rajabasa Bandar Lmpung) TP 2012/2013 - septia agustina; Irawan Suntoro; Yunisca Nurmalisa (Jurnal Kultur Demokrasi, 2012)
This research focuses on the role of the Integrated Islamic School In Student Religious Character Formation (case Study in SDIT Permata Bunda Gedungmeneng Rajabasa Bandar Lampung) Academic Year 2012/2013. Therefore the aim of this study was to analyze the extent to which medeskripsikan and Role of Integrated Islamic School In Student Religious Character Formation. The method used in this research is descriptive method that is supported by the questionnaire data collection techniques, observation, and interviews. The population consists of 150 students, and a sample taken 20% of the population that is 30 percent of students with data analysis. The results: of the calculation using the percentage formula then categorized research was instrumental Thus the results of these tests can be seen that there is a very strong role and significance between role in the formation of a unified Islamic School student religious character (Case Study in Building meneng SDIT Permata Bunda Rajabasa Bandar) TP 2012/2013 Key words: Integrated Islamic School, Student Religious Character